Pengaruh Penerapan Sistem Informasi Akuntansi, Kualitas Sistem Informasi Akuntansi, Dan Kompleksitas Tugas Terhadap Kinerja Karyawan (Studi Kasus Pada Assalaam Hypermarket) - Mutmainah, Annisa' Fitri; Pardanawati, Sri Laksmi; Utami, Wikan Budi (Jurnal Akuntansi dan Pajak, 2024)
The purpose of this study is to determine the effect of the application of accounting information systems, the quality of accounting information systems, and the complexity of tasks on employee performance. In the preparation of this study using quantitative research types. Primary research data was obtained from respondents through data collection techniques in the form of questionnaires through google forms. The sample used in the study was 81 respondents. This study used descriptive statistical data analysis methods and hypothesis testing multiple linear regression analysis. The results of the research test show that the application of accounting information systems and the complexity of tasks affect the performance of Assalaam Hypermarket employees. While the complexity of the task has no effect on the performance of Assalaam Hypermarket employees.